In vitro assessment of polychlorinated biphenyl bioaccessibility in meat: Influence of fat content, cooking level and consumer age on consumer uptake. (16th April 2022) - Planche, Christelle; Ratel, Jérémy; Mercier, Frédéric; Zhang, Cheng; Angénieux, Magaly; Blinet, Patrick; Marchand, Philippe; Dervilly, Gaud; Albert, Isabelle; Tressou, Jessica; Debrauwer, Laurent; Engel, Erwan
Highlights: An in vitro digestion protocol was set up to assess PCB bioaccessibility in meat. The mean PCB bioaccessibility was 26% in 11% fat ground beef. PCB bioaccessibility and mean uptakes increased when the fat level decreased in meat. PCB bioaccessibility and mean uptakes decreased when meat is well-done cooked. PCB bioaccessibility and mean uptakes were lower in the elderly than in adults. Abstract: In a risk assessment perspective, this work aims to assess the bioaccessibility of PCBs in meat. A standardised in vitro static digestion protocol was set up and coupled with extraction, clean-up and GC × GC-ToF/MS multianalyte method to monitor the fate of PCBs in meat during digestion. Starting with spiked meat, PCB bioaccessibility in 11% fat medium-cooked meat varied in adults from 20.6% to 30.5% according to congeners. PCB bioaccessibility increased to 44.2–50.1% in 5% fat meat and decreased to 6.2–9.1% and to 14.6–19.4% in digestion conditions mimicking infants and elderly, respectively. Intense cooking also decreased PCB bioaccessibility to 18.0–26.7%. Bioaccessibility data obtained with spiked meat were validated with measurements carried out in incurred meat samples. Finally, mean uptake distributions are obtained from a modular Bayesian approach. These distributions feature a lower mode when the fat content is higher, the meat is well-done cooked, and the consumers are older.